2019
DOI: 10.1111/1750-3841.14481
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Volatile Profiles of Six Popular Edible Mushrooms Using Headspace‐Solid‐Phase Microextraction Coupled with Gas Chromatography Combined with Chemometric Analysis

Abstract: The classification of six mushroom species (white beech, brown beech, button, oyster, king oyster, and enoki mushrooms) was successfully achieved using canonical discriminant analysis (CDA) on volatile metabolite data sets obtained by headspace‐solid‐phase microextraction gas chromatography (HS‐SPME‐GC). Twenty‐seven major volatile compounds in six edible mushrooms were positively identified by HS‐SPME‐GC mass spectroscopy. The total volatile content was highest in brown beech mushroom (P < 0.05). Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
5
17
0
Order By: Relevance
“…Nevertheless, concentrations of the volatiles (i.e., compounds included in Tables 2 and 3) were higher in P. ostreatus compared to P. eryngii (1684 ± 591 vs. 965.4 ± 321.5 µg/g f.w), in agreement with the data reported by Jung et al ( 2019) [2]. The compounds detected in fresh samples are classified as aldehydes, alcohols, ketones, alkanes, fatty acid methyl esters (FAME) and terpenes.…”
Section: Total Volatiles Contentssupporting
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, concentrations of the volatiles (i.e., compounds included in Tables 2 and 3) were higher in P. ostreatus compared to P. eryngii (1684 ± 591 vs. 965.4 ± 321.5 µg/g f.w), in agreement with the data reported by Jung et al ( 2019) [2]. The compounds detected in fresh samples are classified as aldehydes, alcohols, ketones, alkanes, fatty acid methyl esters (FAME) and terpenes.…”
Section: Total Volatiles Contentssupporting
confidence: 91%
“…Heptanal, 2-hexenal, phenylacetaldehyde, 2,4-nonadienal, and 2,4 decadienals were also present in the volatiles of both mushroom species, at slightly higher concentrations in P. eryngii; finally, nonanal, undecenal and 3-dodecenal were detected only in P. eryngii, while 2-phenyl-2-butenal was recorded only in P. ostreatus. The aldehydes identified in this study have been previously reported in several mushroom species [2,17,29,40].…”
Section: Aldehydessupporting
confidence: 78%
See 1 more Smart Citation
“…It is defined as the ratio of the chromatographic peak area response to the SPME extraction of 10 mL of standard solution (10 µg/L) to that with direct injection of 1 µL of standard solution (10 mg/L) [50]. HS-SPME experiments were performed under respective optimized conditions [51][52][53][54]. As can be seen from Table S1 (Supplementary Materials), the fiber has a high enrichment efficiency for two-ring PAHs, long-chain aliphatic alcohols and alkanes, and the lowest enrichment effect was obtained for benzyl alcohol because benzyl alcohol is the most polar analyte.…”
Section: Extraction Characteristics Of Copolymer Coatingmentioning
confidence: 99%
“…With respect to the second question raised, we can point out that Reference [19] demonstrated that the species of fungi of the genus Penicillium could be discriminated between by means of an analysis of volatile secondary metabolites. Moreover, a gas chromatography–mass spectrometry (GC–MS) evaluation of different species of fungi [20,21,22] made evident that the chemical structures of many of these metabolites are similar to those of known fragrance chemicals. In Reference [6], a table showed more than 150 types of aromatic components present in mushrooms related to one or several odors.…”
Section: Introductionmentioning
confidence: 99%